PENGEMBANGAN APLIKASI ASTRON SEBAGAI MEDIA PEMBELAJARAN MATERI SISTEM TATA SURYA DI KELAS VI SD - Kamal Aramdan Akbar; Regina Lichteria Panjaitan; Rana Gustian Nugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop and assess the validity and practicality of the ASTRON application as an interactive learning medium for solar system material in sixth-grade elementary school. The development of this application was motivated by students’ difficulties in understanding abstract concepts such as the Earth's rotation, planetary revolution, and planetary characteristics, which cannot be directly observed. In addition, the development was also driven by the need for interactive learning media that align with technological advancements to support a more effective learning process. The research employed a Research and Development (R&D) method using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The product was validated by six validators, consisting of three subject matter experts and three media experts, with validation results of 94.61% and 91.29%, respectively—both categorized as very valid. Practicality testing was conducted in three stages: individual trials (91%), small group trials (90%), and large group trials (99%), all of which indicated the very practical category. The ASTRON application contains interactive multimedia content, including text-based material, illustrative images, instructional videos, quizzes, and educational games. It was developed based on constructivist and behaviorist learning theories, Mayer’s multimedia theory, and the VAK learning style approach (Visual, Auditory, Kinesthetic). The results indicate that the ASTRON application is feasible and practical to use as a learning medium that can enhance student engagement and motivation in learning about the solar system.